Ethical Leadership in Comparative Perspective - Ashath, Mohamed; Insaf, Mohammed; Aroos, Ashker (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
This article delves into the shared ethical paradigms between Buddhism and Islam, as epitomized by the governance models of King Aśoka and ʿUmar ibn ʿAbd al-ʿAzīz. Both leaders are widely celebrated for their profound commitment to justice, compassion, and inclusivity, which formed the cornerstone of their approaches to nation-building. King Aśoka, guided by the principles of Dhamma, prioritized non-violence, religious tolerance, and public welfare, transforming his empire into a beacon of ethical governance. Similarly, ʿUmar ibn ʿAbd al-ʿAzīz often hailed as the "Fifth Rightly Guided Caliph," implemented policies grounded in Islamic principles of equity, accountability, and social justice, fostering trust and harmony among diverse communities under his rule. By examining these historical examples, this study identifies key lessons for contemporary Sri Lanka, a nation striving to reconcile its rich religious and cultural diversity with the challenges of inter-communal harmony. This research applies library-based qualitative methodology, in which the researchers use data that includes textual analysis of written materials such as books, journal articles, and internet sources. The findings underscore the enduring relevance of ethical governance rooted in shared values to address socio-economic disparities, promote unity, and achieve sustainable development. This comparative analysis not only highlights the universal applicability of their principles but also offers a blueprint for fostering peace and equity in pluralistic societies like Sri Lanka.